Advanced Intelligent Big Data Analytic-Based Automated Layout for Environmental Design Intelligent Sensor Networks. (22nd July 2022) - Yu, Xueyong; Yu, Heng; Liu, Chunjing
Abstract : In this paper, through the in-depth study of advanced intelligent extensive data analysis and the design of the model of the environment design automatic layout intelligent sensor network, we realize the environment design intuitive layout smart sensor network based on advanced thoughtful and extensive data analysis. According to the non-beacon-enabling CSMA/CA algorithm of the MAC layer of a single node in intelligent sensor network, the analysis model of the node MAC layer of the innovative sensor network based on the Markov chain is established. The mathematical calculation method of node MAC layer delay is obtained through the analysis and calculation of nodes' Markov state transfer process in this model. By analyzing the internal composition of design grooming, data support, analysis modeling, and platform in environmental design big data and the relationship between each part, the industrial extensive data analysis modeling method system is formed based on the CRISP-DM model, based on which the demand analysis of the industrial comprehensive data analysis modeling platform is carried out, and the overall architecture of the platform is formed; this paper proposes an automatic layout algorithm based on strategy iteration for each. Each type of environment design is modeled, and the layout scheme is sequentially generated. The applicability, aesthetics, and comfort are considered, but the design information provided by the space contour can be regarded to develop a reasonable layout scheme. The experimental results show the rationality and versatility of the automatic layout schemes, proving the practicality and time-saving nature of the work.